State of Quality 4.0 in the South African chrome mining industry: Gap analysis and priority areas for improvement - Matolwandile Mzuvukile Mtotywa; Thabisile Dube (Cogent Business & Management, 2023)
The aim of the study was to understand the state of Quality 4.0 in the chrome mining industry and to use gap analysis to identify priority improvement areas. This study adopted a post-positivist paradigm, with a cross-sectional quantitative research design using a survey within the mining industry. The responses (n = 211) represented a response rate of 74.8%. The results show a composite score, MIDj = 17.80, with QMIj = 50.9%, indicating that the mines were in an initial or ad hoc activity stage but are migrating towards an established, focused process stage. Confirmatory tetrad analysis indicates a reflective model, with an acceptable model fit, SRMR = 0.068. A one sample t-test confirmed that all dimensions of Quality 4.0 had statically significantly lower mean scores than the ideal profile of 5.0 with a large effect size. This study provides an effective approach for quality management practitioners, process owners, and management to effectively assess the progress of Quality 4.0 implementation and identify gaps for improved performance. Identified priority areas for improvement are management commitment to technology and innovation-driven operations, technology-driven employee involvement and empowerment, and process and systems integration. The study provides a comprehensive approach to conducting gap analysis and contributes to the growing body of knowledge on Quality 4.0.
Keywords: 650; efficiency; mining industry; performance; productivity; Quality 4.0